Pendidikan Multikultural dalam Desain Kurikulum dan Pembelajaran Keagamaan Islam - Abdurrahmansyah, Abdurrahmansyah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2017)
Multicultural Education In Curriculum Design and Islamic Religious Learning. Multicultural education is a contemporary educational paradigm that needs to be responded by Islamic educational institutions. As a religion, Islam has a very strong root of multicultural education. In the context of Indonesia, the concept of Bhinneka Tunggal Ika is a collective agreement on the values of universal unity in diversity living with the values of rahmatan lil ‘alamin that need to be developed through practices and traditions of Islamic education in Indonesia. Integrative design of curriculum and learning becomes one of the important alternatives considered as an effort to instill multicultural values through the school system. The open attitude of the teachers, the availability of teaching materials, the supportive school environment, and the pattern of teacher training with multicultural insight become the supporting factors of effective implementation of multicultural education in schools and madrasah.